Teaching academic reading as a disciplinary knowledge practice in higher education - bharuthram, sharita; clarence, sherran (South African Journal of Higher Education, 2016)
Many university lecturers expect students to be able to read disciplinary texts at the appropriate levels, and reflect critically and multidimensionally on those texts, yet are often frustrated by many students’ lack of ability to do so satisfactorily. While there is much research to suggest that academic writing needs to be taught within the disciplines as a practice linked to disciplinary knowledge, there is less research to make the same claims about academic reading which is often referred to, rather, as a ‘skill’. This paper argues for an overt focus on critical academic reading as part of disciplinary teaching and learning and draws on a case study and lecturers’ responses to questions on critical reading to show how an academic literacies and knowledge-focused approach can be useful to lecturers trying to help their students read in the disciplines.